Application of Virtual Reality Tourism for Consumer Satisfaction in Marketing Activities - Nanik Hariyana; Nurjanti Takarini (Nusantara Science and Technology Proceedings, 2022)
The tourism sector has always faced both praise and criticism due to the negative environmental impacts associated with travel and activities at tourist destinations. Therefore, management researchers must identify environmentally friendly tourism solutions that minimize the negative effects of these tours while still being profitable. In particular, virtual reality tourism (VRT) has emerged as a new trend, especially after the COVID-19 pandemic. This form of digital travel has captured the interest of many governments seeking sustainable tourism options. However, the perceptions and motivations of consumers regarding the use of VRT as a sustainable tourism solution are not yet fully understood. To address this research gap, the study aims to leverage expectancy theory and propose goal difficulty and reduced tourism environmental impact (REI) as hope-related motivations. Achievement is considered a motivation related to tools, while willingness to take action to achieve results is seen as motivation related to valence. The researchers anticipate that these motivations will drive two outcomes: low-effort and high-effort pro-environmental behavior. By analyzing data collected from 350 individuals residing in the East Java region, the study found support for all positive associations, except for the relationship between goal difficulty and pro-environmental behavior, as well as between REI and both pro-environmental behaviors. The study also examines and confirms the moderating effect of the number of children in a household and everyday green behavior on some of the proposed associations. These findings provide valuable insights for future research and practical applications in the tourism sector.